Relational anatomy: dissecting and memorialising the dead in medical education - Hallam, E (Medicine Anthropology Theory, 2017)
Relational dimensions of contemporary anatomy, as a body of knowledge and a field of material practices, are examined in this article, focusing on the treatment and uses of bodies after death in anatomical education. Attending to the intersection of the social, the material (including human bodies), and the conceptual, the article draws on anthropological research in medical school settings in Scotland to analyse anatomy as a relational process. This process shapes and constitutes the social relations of the deceased who have donated their bodies to medical education, the relations between human bodies and the different media used in the teaching and learning of anatomy, and the anatomical relations that are examined and visualised within bodies as students develop their knowledge of anatomy. This process also constitutes each body donor, over time, as deceased person, anonymous body or cadaver, ‘material’ for learning, and an instance of human anatomy. With reference to practices at the University of Aberdeen in the last decade – and placing these in the context of wider anthropological debates and developments in anatomy teaching – I explore the anatomising of bodies from the arrival of the recently deceased at the medical school, to their use in the dissecting room, and their subsequent memorialisation by family and friends when returned for burial or cremation. With this movement, bodies after death are valued as persons, as materials for the generation and communication of anatomical knowledge, and as gifts for the advancement of medical science. This constitution of meaning and value informs the perceived affective potential of human remains and the responses they evoke in the living.